Taxation I Simplified A textbook for C.P.A,C.P.S and K.A.T Taxation papers - Nisar Ahmed Saleemi 2001; Walters, Martin; Trotman, Felicity (Nairobi Saleemi, 2001)
Presents an illustrated dictionary of earth science terms.
Previosuly published under title: The illustrated dictionary of earth sciences. 1991.
Keywords: Earth sciences -- Dictionaries, Juvenile; Earth sciences -- Dictionaries